Respuesta :

Answer:

[tex]\begin{array}{|l|l|c|c|c|}\cline{1-5} \textbf{Equation} & \textbf{Standard Form} & \textbf{a} & \textbf{b} & \textbf{c}\\\cline{1-5} \text{1.}\:\:x^2+x=20 & x^2+x-20=0 & 1 & 1 & -20\\\cline{1-5} \text{2.}\:\:4x^2-2x=28 \phantom{)))}& 4x^2-2x-28=0 \phantom{)))}& 4 & -2 & -28\\\cline{1-5} \text{3.}\:\:5x^2=225 & 5x^2-225=0 & 5 & 0 & -225\\\cline{1-5} \text{4.}\:\:x^2-x=36 & x^2-x-36=0 & 1 & -1 & -36\\\cline{1-5} \text{5.}\:\:3x^2-4=7x & 3x^2-7x-4=0 & 3 & -7 & -4 \\\cline{1-5}\end{array}[/tex]

Step-by-step explanation:

Standard form of a quadratic equation:

[tex]\boxed{ax^2+bx+c=0}[/tex]

Question 1

Given:

[tex]x^2+x=20[/tex]

Rearrange to standard form by subtracting 20 from both sides:

[tex]\implies x^2+x -20=20-20[/tex]

[tex]\implies x^2+x -20=0[/tex]

Therefore:

  • a = 1
  • b = 1
  • c = -20

Question 2

Given:

[tex]4x^2-2x=28[/tex]

Rearrange to standard form by subtracting 28 from both sides:

[tex]\implies 4x^2-2x-28=28-28[/tex]

[tex]\implies 4x^2-2x-28=0[/tex]

Therefore:

  • a = 4
  • b = -2
  • c = -28

Question 3

Given:

[tex]5x^2=225[/tex]

Rearrange to standard form by subtracting 225 from both sides:

[tex]\implies 5x^2-225=225-225[/tex]

[tex]\implies 5x^2-225=0[/tex]

Therefore:

  • a = 5
  • b = 0
  • c = -225

Question 4

Given:

[tex]x^2-x=36[/tex]

Rearrange to standard form by subtracting 36 from both sides:

[tex]\implies x^2-x-36=36-36[/tex]

[tex]\implies x^2-x-36=0[/tex]

Therefore:

  • a = 1
  • b = -1
  • c = -36

Question 5

Given:

[tex]3x^2-4=7x[/tex]

Rearrange to standard form by subtracting 7x from both sides:

[tex]\implies 3x^2-4-7x=7x-7x[/tex]

[tex]\implies 3x^2-4-7x=0[/tex]

[tex]\implies 3x^2-7x-4=0[/tex]

Therefore:

  • a = 3
  • b = -7
  • c = -4
ACCESS MORE